2021
DOI: 10.1186/s12937-021-00706-4
|View full text |Cite
|
Sign up to set email alerts
|

Food marketing and gender among children and adolescents: a scoping review

Abstract: Background Pervasive marketing of unhealthy foods is a contributing factor to the growth of the global epidemic of childhood and adolescent overweight and obesity. Sex and gender differences come into play in the design of and responses to these marketing strategies, contributing to the perpetuation of stereotyped behavior and generating disparities in food choices and health. The purpose of this paper is to review the current literature regarding gender differences in food marketing design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 58 publications
3
12
0
2
Order By: Relevance
“…73,74 It may also be possible that males are targeted by industry marketing practices more often than females, as males are reportedly featured more frequently in food marketing, which could lead to greater persuasion towards consuming the product. 75 We also found that individuals classi ed as ethnic minorities were more likely to report the consumption of fast food than ethnic majorities. Recent data has suggested that Black and Hispanic youth in US are being disproportionally exposed more food marketing, which brings concern as socioeconomic status is associated with ethnic minority status in countries like the US, and those with a lower socioeconomic status are more likely to exhibit poorer health outcomes.…”
Section: Discussionmentioning
confidence: 51%
“…73,74 It may also be possible that males are targeted by industry marketing practices more often than females, as males are reportedly featured more frequently in food marketing, which could lead to greater persuasion towards consuming the product. 75 We also found that individuals classi ed as ethnic minorities were more likely to report the consumption of fast food than ethnic majorities. Recent data has suggested that Black and Hispanic youth in US are being disproportionally exposed more food marketing, which brings concern as socioeconomic status is associated with ethnic minority status in countries like the US, and those with a lower socioeconomic status are more likely to exhibit poorer health outcomes.…”
Section: Discussionmentioning
confidence: 51%
“…The scoping review by Castronuovo et al revealed that gender can play an important role in the development of different food marketing techniques and how youth respond to them; many variables could mediate the association between advertising, gender, and eating behaviors, such as weight status, nutritional knowledge, advertising techniques, media type, brand awareness, family pressures, etc. [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with other studies, Greek preadolescent boys were found to be more susceptible to soft drinks and other less healthy beverages compared to girls [ 33 , 34 ]. It is supported that young girls tend to have healthier dietary habits than boys [ 35 ], and this could be partly attributed to the fact that boys are more exposed to food advertising, and their tastes are more influenced by this exposure, which coincides with male-dominant advertisement content [ 36 ]. Moreover, the literature findings suggest that physiological, psychological and sociocultural factors determine the associations between gender and dietary behaviors.…”
Section: Discussionmentioning
confidence: 99%